Disease status, patient quality of life and healthcare resource use for ulcerative colitis in the UK: an observational study. Issue 3 (24th January 2014) - Vaizey, Carolynne J; Gibson, Peter R; Black, Christopher M; Nicholls, Rebecca J; Weston, Adèle R; Gaya, Daniel R; Sebastian, Shaji; Shaw, Ian; Lewis, Stephen; Bloom, Stuart; Gordon, John N; Beale, Amanda; et al.
Abstract : Background: Ulcerative colitis is a lifelong, chronic, relapsing-remitting disease. Objective: To assess the relationship between ulcerative colitis disease status and patient quality of life, and to determine the impact of ulcerative colitis on healthcare costs and work productivity, in the UK. Methods: Clinicians assessed 173 adult patients' current disease status at a single study visit using the partial Mayo (pMayo) instrument. Patients completed the Euro Quality of Life 5-dimension, 5-level (EQ-5D-5L) questionnaire, the Work Productivity and Activity Impairment (WPAI) questionnaire. Healthcare resource use was determined from questionnaires and from patients' medical charts. Results: Patients in remission had a significantly higher EQ-5D-5L scores (mean (SD) 0.86 (0.15)) than patients with active disease (0.71 (0.20); p<0.001). Patients with mild disease had significantly higher mean (SD) EQ-5D-5L scores than patients with moderate/severe disease: 0.77 (0.11) and 0.66 (0.24), respectively (p<0.001). The mean percent productivity impairment was greater for patients with active disease than for patients in remission on all items of the WPAI questionnaire: 24.6% vs 1.8% for work time missed, 34.1% vs 12.9% for impairment while working, 40.8% vs 14.4% for overall work impairment and 42.7% vs 13.0% for activity impairment (p<0.001 for all comparisons). The mean (SD) total cost of healthcare for ulcerative colitis in the prior 3 months was £1211 (1588). Conclusions: When compared with patients in remission, patients with active ulcerative colitis have significantly worse quality of life and significantly more work impairment. The healthcare costs of ulcerative colitis are considerable.